2016
DOI: 10.1002/ase.1657
|View full text |Cite
|
Sign up to set email alerts
|

The effect of image quality, repeated study, and assessment method on anatomy learning

Abstract: The use of two-dimensional (2D) images is consistently used to prepare anatomy students for handling real specimen. This study examined whether the quality of 2D images is a critical component in anatomy learning. The visual clarity and consistency of 2D anatomical images was systematically manipulated to produce low-quality and high-quality images of the human hand and human eye. On day 0, participants learned about each anatomical specimen from paper booklets using either low-quality or high-quality images, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
3
0
2
Order By: Relevance
“…In this vein, Estai and Bunt (2016) found that the importance of teaching modern anatomy is to use a wide selection of pedagogical methods, though more research is needed to investigate this transition to new methodologies. Game-based teaching models that use both visual and auditory stimuli to benefit different learning styles while also encouraging group discussion and participation are among the most recent approaches used (Gallegos et al, 2017), whereas others such as an interactive atlas (Guy et al, 2018), virtual reality (Fenesi et al, 2016;Moro et al, 2017) or even comics (Kim et al, 2017) are also used.…”
Section: Introductionmentioning
confidence: 99%
“…In this vein, Estai and Bunt (2016) found that the importance of teaching modern anatomy is to use a wide selection of pedagogical methods, though more research is needed to investigate this transition to new methodologies. Game-based teaching models that use both visual and auditory stimuli to benefit different learning styles while also encouraging group discussion and participation are among the most recent approaches used (Gallegos et al, 2017), whereas others such as an interactive atlas (Guy et al, 2018), virtual reality (Fenesi et al, 2016;Moro et al, 2017) or even comics (Kim et al, 2017) are also used.…”
Section: Introductionmentioning
confidence: 99%
“…The contemporary educational system includes skills and competences that are required for modern economy (Jirgensons & Kapenieks, 2018). New technologies play a very important and powerful role in all areas of human activities (Fenesi, Mackinnon, Cheng, Kim, & Wainman, 2017). It is clear that they comprise and/or transform different spheres of medicine and medical education (Starkey, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Butcher () directly addressed the issue of image complexity for learning, and demonstrated strong support for the benefit of simpler diagrams designed to highlight the representation of critical relationships, particularly for low knowledge learners. At a given level of image complexity, Fenesi et al () found that image quality itself seemed to have only a limited effect on anatomy learning, and the advantage of higher quality images did not apply with additional learning opportunities. The images in the active learning exercises used in this study varied in complexity, from schematic representations to radiological images; if the images had been systematically ordered by complexity or fidelity, or had been designed specifically to represent spatial or conceptual relationships, it is possible that the positive effect of the image‐based active learning exercises might have been even stronger.…”
Section: Discussionmentioning
confidence: 99%